Measurement of global and direct normal solar energy radiation in Seri Iskandar and comparison with other cities of Malaysia - Mohammad, S.T. (Elsevier Ltd, 2020)
Potential solar data are an essential tool for successful solar design and application. However, because of the limited availability of solar radiation stations, spatial resolution is affected whenever an attempt to construct a solar radiation map is made. In this paper, actual solar data were acquired in Universiti Teknologi PETRONAS (UTP), Seri Iskandar, Malaysia (4Â°24â²latitude, 100Â°58â²E longitude, 24 m altitude). The measurements of global solar radiation and direct normal radiation were gathered and analyzed for the whole of 2018. In addition to solar data collection, real-time solar radiation, high accuracy, and related meteorological data were also obtained. With 1-min recorded average values the everyday and monthly solar radiation averages were determined. A record of 1068.10 W/m2 as maximum daily global solar radiation and 915 W/m2 for direct normal radiation was observed on 9 September 2018. Discussions on daily and monthly average clearness index differences are also elaborated in this paper. The acquired data were compared with corresponding data obtained from other selected Malaysian cities and the widely useable data resource, the NASA solar energy model and surface meteorology. Investigation of the data indicated that Seri Iskandar obtains an ample amount of global solar radiation, indicating the strong potential for the use of solar energy. Â© 2020 The Authors.